Chemical composition and cycling of dissolved organic matter in the Mid-Atlantic Bight - Aluwihare, L. I.; Repeta, D. J.; Chen, R. F. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2002)
This study focuses on the chemical characterization of high molecular-weight dissolved organic matter (HMW DOM) isolated from the Middle Atlantic Bight in April 1994 and March 1996. Using proton nuclear magnetic resonance spectroscopy ((HNMR)-H-1) and monosaccharide analysis we compared both spatial and temporal variations in the chemical structure of HMW DOM across this region. Our analyses support the presence of at least two compositionally distinct components to HMW DOM. The major component is acyl polysaccharide (APS), a biopolymer rich in carbohydrates, acetate and lipid, accounting for between 50% and 80% of the total high molecular-weight dissolved organic carbon (HMW DOC) in surface samples. APS is most abundant in fully marine, surface-water samples, and is a product of autochthonous production. Organic matter with spectral properties characteristic of humic substances is the second major component of HMW DOM. Humic substances are most abundant (up to 49% of the total carbon) in samples collected from estuaries, near the coast, and in deep water, suggesting both marine and perhaps terrestrial sources. Radiocarbon analyses of neutral monosaccharides released by the hydrolysis of APS have similar and modern (average 71parts per thousand) Delta(14)C values. Radiocarbon data support our suggestion that these sugars occur as part of a common macromolecule, with an origin via recent biosynthesis. Preliminary radiocarbon data for total neutral monosaccharides isolated from APS at 300 and 750m show this fraction to be substantially enriched relative to total HMW DOC and DOC. The relatively enriched radiocarbon values of APS at depth suggest APS is rapidly transported into the deep ocean. (C) 2002 Elsevier Science Ltd. All rights reserved.
607kxTimes Cited:74Cited References Count:44